Види родини Poaceae, описані з України: роди Helictotrichon Besser, Hierochloë R. Br., Koeleria Pers., Lolium L., Melica L., Milium L., Molinia Schrank, Panicum L - Федорончук, М.М.; Губарь, Л.М.; Футорна, О.А. (Український ботанічний журнал, 2013)
Приведен список видов семейства Poaceae (роды Helic totrichon, Hierochloë, Koeleria, Lolium, Melica, Milium, Molinia, Pa nicum), описанных с территории Украины, осуществлена типификация большинства видов. Для каждого вида указаны основная синонимика, номенклатурный тип (по протологу и голотип, лектотип,изотип, неотип или топотип), автор его выделения и место хранения. The list of species of vascular plants of the family Poaceae (genera Helictotrichon, Hierochloë, Koeleria, Lolium, Melica, Milium, Molinia, Panicum) described from Ukraine and typification of some species are provided. The following data for each species are provided: basionym, original nomenclatural citation; type according to the protologue, and holotype, isotype, lectotype, neotype, or topotype; herbarium(-a) in which the specimen(s) is (are) deposited.